Swing shift : "all-girl" bands of the 1940s - Tucker, Sherrie, 1957- (e-Duke books scholarly collection., 2000)
The story, based on extensive individual interviews, of the women's swing bands that toured extensively during World War II and after -- a kind of "League of their Own" for jazz